Tebentafusp, a T cell engager, promotes macrophage reprogramming and in combination with IL-2 overcomes macrophage immunosuppression in cancer - Güç, Esra; Treveil, Agatha; Leach, Emma; Broomfield, Anna; Camera, Antonio; Clubley, James; Nieto Garcia, Paula; Kazachenka, Anastasiya; Khanolkar, Rahul; del Carpio, Luis; Heyn, Holger; Hassel, Jessica C.; et al. (Nature Communications, 2025)
Uveal melanoma (UM) is the most common intraocular cancer in adults, with metastatic disease (mUM) occurring in approximately half of the patients. Tebentafusp, an immune-mobilizing monoclonal T cell receptor against cancer (ImmTAC), is a therapeutic shown to improve overall survival (OS) in HLA-A*02:01+ adult patients with mUM. Here we investigate the impact of tumor-associated macrophages (TAM) on ImmTAC activity. In vitro, M2 macrophages inhibit ImmTAC-mediated tumor-killing in a dose-dependent and contact-dependent manner. Accordingly, high baseline intratumoral TAM-to-T cell ratios correlate with shorter OS (HR = 2.09, 95% CI, 1.31-3.33, p = 0.002) in tebentafusp-treated mUM patients from a phase 2 trial. By contrast, IL-2 conditioning of T cells overcomes M2 macrophage-mediated suppression in vitro, while ImmTAC treatment leads to M2-to-M1 macrophage reprogramming both in vitro and in tebentafusp-treated mUM patients. Overall, we show that tebentafusp reshapes the tumor microenvironment to enhance anti-tumor T cell activity, whilst combining tebentafusp with IL-2 may enhance benefit in patients with high levels of TAM.
Online veröffentlicht: 10. März 2025
Gesehen am 05.11.2025